Lithium-based bentonite as well as preparation method and application thereof
Through electrostatic acid treatment and lithium exchange treatment, the (001) crystal plane spacing of bentonite is modified to form lithium-based bentonite, which solves the problem of insignificant improvement of the conductivity of lithium-ion batteries and achieves the high conductivity and safety performance of lithium-ion batteries promote.
Patent Information
- Application Number
- CN202310786923.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, the conductivity of lithium-ion batteries is not significantly improved, and the separator process of lithium-sulfur batteries is complex, which limits the application direction.
Through electrostatic acid treatment and lithium exchange treatment, the (001) crystal plane spacing of modified bentonite increases by 10-50%, which increases the lithium ion content and ion conductivity, forms lithium-based bentonite, and applies it to lithium-ion batteries.
It significantly improves the conductivity and safety performance of lithium-ion batteries, simplifies the process flow, and enhances the magnification and safety performance of lithium-ion batteries.
Smart Images

Figure CN119275329A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrode materials, and in particular to lithium-based bentonite and a preparation method and application thereof. Background Art
[0002] Bentonite is a mineral material with large surface area, expansion performance, heat resistance and adsorption performance. Its main component is montmorillonite. The content of montmorillonite in bentonite affects the performance of bentonite. Montmorillonite is a 2:1 type layered silicate mineral composed of two silicon-oxygen tetrahedrons sandwiching one aluminum-oxygen octahedron. Modified bentonite can obtain considerable electrochemical properties and better mechanical properties. The modification methods of bentonite include sodium modification, acid modification, roasting activation modification and organic modification.
[0003] The traditional concept is to grind or centrifuge the mineral material to obtain a nanoscale slurry and coat it on the battery diaphragm, or to obtain a modified material through ion exchange of the mineral material and then coat the diaphragm, or to mix the mineral material with the electrolyte matrix, the lithium-containing cathode material, and the ion-conducting salt to obtain a composite solid electrolyte. However, since the bentonite material itself is a flaky structure, the conductivity is low in the direction perpendicular to the lamellae, and there is anisotropy, so the effect of improving the conductivity when used directly is not obvious or even counterproductive. Ion exchange-modified bentonite is mostly used in sodium ion batteries, and is less used in lithium ion batteries. In addition, ion exchange is only to exchange a small amount of cations between the layers of bentonite with cations in the exchange agent, which will not change the layered structure, so it is still anisotropic after modification, and the conductivity is not significantly improved. However, the process of processing mineral materials into composite materials is cumbersome, the structure of the composite materials is complex, and the reprocessing performance is poor, which limits the application direction.
[0004] CN113711434A discloses a separator for lithium-sulfur battery and a lithium-sulfur battery comprising the separator for lithium-sulfur battery. Montmorillonite with specific ion exchange is made into an organic coating, which is coated on the separator to adsorb lithium polysulfide and improve the capacity and life of the lithium-sulfur battery. However, ion exchange only exchanges the cations in bentonite with the cations in the exchange agent, and does not change the layered structure. Therefore, the modified structure is still anisotropic, and the conductivity is not significantly improved.
[0005] CN114843598A discloses a solid electrolyte and its preparation method and application, wherein a composite solid electrolyte is obtained by mixing mineral materials with an electrolyte matrix, a lithium-containing cathode material, and an ion-conducting salt, thereby optimizing the interface reaction between the solid electrolyte and the cathode and cathode of the battery and improving the safety of the battery. However, the process of processing mineral materials into composite materials is cumbersome, the composite material structure is complex, and the reprocessing performance is poor, which limits the application direction. Summary of the invention
[0006] The purpose of the present invention is to overcome the problem of insignificant improvement in conductivity in the prior art, and to provide lithium-based bentonite and a preparation method and application thereof. The lithium-based bentonite has a simple structure, can be used in lithium-ion batteries and significantly improves conductivity. At the same time, the present invention uses acid treatment and lithium exchange through electricity, and the treatment method is simple.
[0007] In order to achieve the above object, the first aspect of the present invention provides a lithium-based bentonite, wherein the (001) crystal plane spacing of the lithium-based bentonite is 10-50% larger than the (001) crystal plane spacing of bentonite.
[0008] A second aspect of the present invention provides a method for preparing lithium-based bentonite, the preparation method comprising:
[0009] In the presence of an acidifier, the bentonite is subjected to an acid treatment to obtain an acidified bentonite; wherein the voltage of the acid treatment is 5-15V;
[0010] The acidified bentonite is subjected to lithium exchange treatment with a lithiating agent to obtain lithium-based bentonite.
[0011] The third aspect of the present invention provides lithium bentonite obtained by the aforementioned preparation method.
[0012] A fourth aspect of the present invention provides use of the aforementioned lithium-based bentonite in a lithium-ion battery.
[0013] A fifth aspect of the present invention provides a lithium-based bentonite dispersion, comprising lithium-based bentonite and a dispersant; wherein the lithium-based bentonite is obtained by grinding the aforementioned lithium-based bentonite.
[0014] A sixth aspect of the present invention provides use of the aforementioned lithium-based bentonite dispersion in a lithium-ion battery.
[0015] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0016] 1) The (001) crystal plane spacing of the lithium-based bentonite is 10-50% larger than that of bentonite, so that the lithium-based bentonite has a higher lithium ion content and higher ion conductivity, and can be used in lithium-ion batteries to improve battery rate and safety performance.
[0017] 2) The method of the present invention uses an acid treatment to destroy the Al-O bond in the bentonite structure, increase the (001) crystal plane spacing by 10-50%, dissolve aluminum ions, and also dissolve other interlayer cations and increase defects, providing vacancy channels for the movement of conductive ions; the defects caused by the acid treatment of the bentonite cause the bentonite to change from high anisotropy to low anisotropy, which is more conducive to the subsequent transmission of lithium ions; and then undergo lithium exchange treatment to make Li + Exchange Al3+ , entering the bentonite lattice, so that the obtained lithium-based bentonite has a higher lithium ion content and a higher ion conductivity, and can be used in lithium-ion batteries.
[0018] 3) The lithium-based bentonite of the present invention replaces high-valent ions such as calcium, magnesium, and aluminum with low-valent lithium ions, and the surface of the crystal layer carries a negative charge, so it has adsorption properties and can adsorb metal cations. Lithium-based bentonite is added to lithium-ion batteries as a solid electrolyte to effectively adsorb metal ions dissolved from the positive electrode, preventing the metal ions from penetrating to the negative electrode side and being reduced to metal particles that pierce the diaphragm to cause a battery short circuit, thereby improving the safety performance of the battery.
[0019] 4) The lithium-based bentonite of the present invention has high electrical conductivity and stable chemical properties. When preparing all-solid-state batteries and hybrid solid-liquid lithium-ion batteries, it can be added to the battery system as a solid electrolyte to improve the battery energy density.
[0020] 5) The lithium-based bentonite of the present invention can be used to prepare a lithium-based bentonite dispersion with stable particle size, which is not easy to settle and has a stable solid content. It is used for positive and negative electrode blending and diaphragm coating of lithium-ion batteries to improve battery rate and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The present invention provides a process flow chart for preparing lithium-based bentonite. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] In a first aspect, the present invention provides a lithium-based bentonite, wherein the (001) crystal plane spacing of the lithium-based bentonite is 10-50% larger than the (001) crystal plane spacing of bentonite, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, and any value in the range consisting of any two values.
[0024] In some preferred embodiments, the (001) interplanar spacing of the lithium-based bentonite is 30-50% greater than the (001) interplanar spacing of bentonite.
[0025] In the present invention, the lithium-based bentonite has a larger (001) crystal plane spacing. As the (001) crystal plane spacing increases, more lithium is exchanged into the bentonite. On the one hand, the lithium content can be increased. On the other hand, the bentonite lattice is destroyed and changes from high anisotropy to low anisotropy, which is more conducive to the transmission of lithium ions.
[0026] In the present invention, the change of (001) crystal plane can characterize the intercalation material. The larger the interplanar spacing, the more lithium has been intercalated into the bentonite structure. The test method is XRD test, which is collected by step scanning. The diffraction beam is removed by a graphite monochromator. β The scanning range (2θ) was 3° to 70°, the step width (2θ) was 0.02°, and the counting time per step was 1 s.
[0027] Bentonite is a non-metallic mineral with montmorillonite as its main mineral component. Montmorillonite is a 2:1 type layered silicate mineral composed of two silicon-oxygen tetrahedrons sandwiching one aluminum-oxygen octahedron, with Na + , Ca 2+ , K + Equivalent cation, its chemical formula is: E x (H2O)4{(Al 2-x Mg x )2[(Si,Al)4O 10 ](OH)2}, where E is Na + , Ca 2+ or K + , x is 0-0.6. The lithium-based bentonite of the present invention is a modified bentonite. The Al-O bond is broken by the electric acid treatment, the aluminum-oxygen octahedral lattice structure is destroyed, and the (001) crystal plane spacing is increased by X-ray diffraction test, so that it has more excellent electrochemical properties and mechanical properties.
[0028] The present invention has found through research that the lithium-based bentonite lattice obtained by electric acid treatment is distorted, and compared with untreated bentonite, XRD test shows that the spacing of the (001) crystal plane increases by 10%-50%.
[0029] The inductively coupled plasma (ICP) test found that the lithium-based bentonite of the present invention has different element contents from the untreated bentonite, especially the aluminum content is significantly reduced, which indicates that the spacing of the (001) crystal plane is increased, the aluminum-oxygen octahedral lattice structure is destroyed, and the dissolved aluminum increases.
[0030] In some embodiments of the present invention, the mass content of lithium in the lithium-based bentonite is 0.6-3wt%, for example, 0.6wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, 2.5wt%, 2.8wt%, 3wt%, and any value in the range of any two values, preferably 2-3wt%.
[0031] In the present invention, the higher the mass content of lithium in the lithium-based bentonite, the greater its ion conductivity.
[0032] In some embodiments of the present invention, the mass content of aluminum in the lithium bentonite is 6-10wt%, for example, 6wt%, 6.5wt%, 6.6wt%, 6.8wt%, 6.89wt%, 7wt%, 7.2wt%, 7.5wt%, 7.8wt%, 8wt%, 8.3wt%, 8.5wt%, 8.8wt%, 9wt%, 9.2wt%, 9.29wt%, 9.3wt%, 9.33wt%, 9.4wt%, 9.45wt%, 9.5wt%, 10wt%, and any value in the range composed of any two values, preferably 6.5-9.5wt%, more preferably 6.8-9.3wt%.
[0033] In the present invention, the aluminum content is controlled within the above range so that the anisotropy of the lithium-based bentonite is reduced, and the bentonite has a higher lithium content, thereby having a higher lithium ion conductivity.
[0034] In the present invention, the lithium element content and the aluminum element content are detected by inductively coupled plasma optical emission spectrometer (ICP-OES).
[0035] In some embodiments of the present invention, the room temperature ionic conductivity of the lithium-based bentonite is 1×10 -4 -8×10 -3 S cm -1 , preferably 1×10 -3 -7×10 -3 S cm -1 .
[0036] In the present invention, the room temperature ionic conductivity of the present invention is measured by making it into a blocking electrode through the AC impedance method.
[0037] In some embodiments of the present invention, the average particle size of the lithium bentonite is 1-100 μm.
[0038] A second aspect of the present invention provides a method for preparing lithium-based bentonite, the preparation method comprising:
[0039] In the presence of an acidifier, the bentonite is subjected to an acid treatment to obtain an acidified bentonite; wherein the voltage of the acid treatment is 5-15V, the current is 0.01-2A, and the acid treatment can be performed using alternating current or direct current;
[0040] The acidified bentonite is subjected to lithium exchange treatment with a lithiating agent to obtain lithium-based bentonite.
[0041] The present invention firstly uses an electric acid treatment method to distort the bentonite lattice and destroy the Al-O bond in the bentonite structure. XRD test shows that the (001) crystal plane spacing increases by 10-50%, so that aluminum ions are dissolved and interlayer cations are dissolved at the same time, increasing defects and providing vacancy channels for the movement of conductive ions. Then, lithium exchange treatment is performed to not only make Li ﹢ Exchange cations between layers and make Li ﹢ Exchange Al 3﹢ , entering the bentonite lattice, so that the obtained lithium-based bentonite has a higher lithium ion content and a lower aluminum ion content, and has a higher ionic conductivity. The aluminum content in the bentonite before and after the electric acid treatment was tested by ICP, and it was determined that the proportion of aluminum dissolved was at most 33% of the original aluminum content; the lithium content in the final product was greater than 0.6% by ICP test, which exceeded the total amount of other exchangeable cations except aluminum ions, indicating that aluminum was successfully dissolved and exchanged.
[0042] The present invention breaks through the fixed thinking of traditional preparation of lithium-based bentonite. Ion exchange can only replace cations existing in the form of ions between bentonite layers. After destroying the bentonite structure by applying an external voltage, the chemical bonds containing covalent components can be destroyed and more cations can be replaced.
[0043] The present invention synthesizes a new material by a lower-cost and more efficient method, and provides a new idea for the synthesis of solid electrolytes.
[0044] In some embodiments of the present invention, the acidulant is a 1-10 mol / L sulfuric acid solution, a hydrochloric acid solution or a nitric acid solution, preferably a 2-8 mol / L sulfuric acid solution.
[0045] In the present invention, the acidifier at this concentration can better destroy the Al-O bond in the bentonite structure, increase the interplanar spacing, dissolve aluminum ions, and also dissolve other interlayer cations and increase defects, providing vacancy channels for the movement of conductive ions.
[0046] In some embodiments of the present invention, the ratio of the hydrogen ion concentration of the acidulant to the metal ion concentration of the bentonite is 8-15:1, preferably 10:1, that is, at the same volume, the hydrogen ion concentration in the acidulant is ten times the metal ion concentration in the bentonite.
[0047] In the present invention, the acidulant can better destroy the Al-O bond in the bentonite structure under this dosage, increase the interplanar spacing, dissolve aluminum ions, and also dissolve other interlayer cations and increase defects, providing vacancy channels for the movement of conductive ions.
[0048] In some embodiments of the present invention, the average particle size of the bentonite is 10-1000 μm.
[0049] In some preferred embodiments of the present invention, the voltage of the acid treatment is 10-15V, the current is 0.1-1A, and the acid treatment uses direct current.
[0050] In the present invention, the Al-O bond in the bentonite structure can be better destroyed under this voltage, the interplanar spacing is increased, aluminum ions are dissolved, other interlayer cations are dissolved and defects are increased, providing vacancy channels for the movement of conductive ions.
[0051] In some embodiments of the present invention, the temperature of the acid treatment is 10-40°C, preferably 25-40°C, and the time is 1-72h, preferably 12-36h.
[0052] In some embodiments of the present invention, the lithiating agent is a 1-10 mol / L lithium hydroxide solution, a lithium acetate solution or a lithium carbonate solution.
[0053] In some embodiments of the present invention, the ratio of the lithium ion concentration of the lithiating agent to the hydrogen ion concentration of the acidified bentonite is 8-15:1, preferably 10:1, that is, under the same volume, the lithium ion concentration in the lithiating agent is ten times the hydrogen ion concentration in the acidified bentonite after electric acid treatment.
[0054] In some embodiments of the present invention, the conditions of the lithium exchange treatment include: a temperature of 10-40° C., preferably 25-40° C., and a time of 1-72 h, preferably 12-36 h.
[0055] In the present invention, by adopting lithium exchange, lithium will replace the positions originally occupied by interlayer cations and aluminum ions in bentonite, so that the lithium-based bentonite has a higher lithium content and thus has a higher lithium ion conductivity.
[0056] In some embodiments of the present invention, a post-treatment step is further included after the lithium exchange treatment, and the post-treatment includes at least washing and drying. For example, the post-treatment includes suction filtration, washing, drying, grinding and sieving. Furthermore, the washing is preferably carried out with distilled water or deionized water; the drying includes oven drying, spray drying or freeze drying.
[0057] In the present invention, washing is a key step. On the one hand, the dissolved metal cations can be removed by washing, and on the other hand, the excess lithium salt in the lithium exchange treatment step can be removed by washing.
[0058] The third aspect of the present invention provides lithium bentonite obtained by the aforementioned preparation method.
[0059] A fourth aspect of the present invention provides use of the aforementioned lithium-based bentonite in a lithium-ion battery.
[0060] The lithium-based bentonite of the invention has high ion conductivity and high lithium ion content and can be used for preparing lithium ion batteries.
[0061] The lithium-based bentonite of the present invention can be added to the negative electrode slurry as a solid electrolyte, or can be coated on the diaphragm as a coating material. Due to the increased lithium content, the application in the negative electrode of a lithium-ion battery can improve the rate performance of the battery. Due to the presence of a large number of lattice defects in the lithium-based bentonite, the thermal stability is improved, and adding it to the diaphragm can improve the safety performance of the battery.
[0062] A fifth aspect of the present invention provides a lithium-based bentonite dispersion, comprising lithium-based bentonite and a dispersant; wherein the lithium-based bentonite is obtained by grinding the aforementioned lithium-based bentonite.
[0063] The lithium-based bentonite of the invention can be used to prepare lithium-based bentonite dispersion with stable particle size, which is used for positive and negative electrode blending or diaphragm coating of lithium-ion batteries to improve battery rate and safety performance.
[0064] In some embodiments of the present invention, the content of lithium bentonite in the lithium bentonite dispersion is 1-80 wt %, preferably 20-50 wt %.
[0065] In some embodiments of the present invention, the dispersant is selected from one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid, sodium polyacrylate, dodecylbenzene sulfonic acid and sodium dodecylbenzene sulfonate.
[0066] In some embodiments of the present invention, the content of the dispersant in the lithium bentonite dispersion is 1-2 wt % of the lithium bentonite.
[0067] In some embodiments of the present invention, in the lithium bentonite dispersion, the particle size of the lithium bentonite is 0.03-1 μm.
[0068] In the present invention, the average particle size of bentonite is 10-1000 μm; in the process of preparing lithium-based bentonite, grinding and screening are required to control the average particle size of the lithium-based bentonite to be 1-100 μm. Within this particle size range, particles are not likely to agglomerate, the powder is not likely to absorb water, and is easy to store; and grinding and screening can prepare for the preparation of dispersion liquid; in the process of preparing lithium-based bentonite dispersion liquid, the particle size of particles in the dispersion liquid can be controlled, so that the average particle size of the lithium-based bentonite in the dispersion liquid is 0.03-1 μm, so that it is easy to disperse in battery electrode slurry.
[0069] In the present invention, the preparation method of the lithium-based bentonite dispersion comprises: grinding the lithium-based bentonite, a dispersant and a solvent (NMP or water) by a sand mill to obtain the lithium-based bentonite dispersion.
[0070] A sixth aspect of the present invention provides use of the aforementioned lithium-based bentonite dispersion in a lithium-ion battery.
[0071] According to a particularly preferred embodiment of the present invention, Figure 1 As shown, the preparation method of lithium bentonite specifically comprises the following steps:
[0072] (1) Acid treatment by electricity: Bentonite is added to an acidifier of 1-10 mol / L, and the hydrogen ion concentration of the acidifier is 8-15 times the metal ion concentration of the bentonite, and the mixture is immersed in electricity at a temperature of 10-40°C and stirred for 1-72 hours to obtain a product 1; the obtained product 1 is filtered, washed with water and dried at low temperature in sequence to obtain a mineral material with obvious layers, namely, acidified bentonite; the temperature of the low temperature drying can be set to 60-85°C and the time can be set to 12-32 hours;
[0073] (2) lithium exchange treatment: adding the acidified bentonite obtained in step (1) into a lithium salt solution, and making the lithium ion concentration in the lithium salt solution 8-15 times the hydrogen ion concentration in the acidified bentonite, soaking and stirring at a temperature of 10-40° C. for 1-72 hours to obtain a product 2, i.e., lithium-exchanged bentonite;
[0074] (3) Post-treatment: The lithium-exchanged bentonite obtained in step (2) is filtered, washed, low-temperature dried, ground and sieved in sequence to obtain lithium-based bentonite with a particle size of 1-100 μm; the low-temperature drying temperature can be set to 60-85° C. and the time can be 12-32 hours.
[0075] The present invention will be described in detail below by way of examples. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not intended to limit the present invention.
[0076] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.
[0077] The following examples are used to illustrate the lithium bentonite and the preparation method thereof of the present invention.
[0078] Example 1
[0079] A method for preparing lithium-based bentonite is carried out according to the corresponding parameters in Table 1, and specifically comprises the following steps:
[0080] (1) Pretreatment: 10 g of bentonite was ground in a mortar and sieved to obtain pretreated bentonite. The test results are shown in Table 1. The initial particle size was 5 μm, the lithium content (PPM) of the raw material in the ICP test was 0, and the aluminum content of the raw material in the ICP test was 9.33%;
[0081] (2) Acid treatment: Bentonite was added to 10 g of 10 mol / L nitric acid under the conditions of an applied current of 100 mA and an applied voltage of 15 V DC, and the acid treatment was carried out for 48 h. The acid-treated product was filtered, washed with water and dried at low temperature to obtain acidified bentonite; wherein the drying temperature was 80° C. and the drying time was 24 h; the aluminum content of the ICP test was 6.33%;
[0082] (3) Lithium exchange treatment: The acidified bentonite obtained in step (2) was added to 50 g of a 2 mol / L lithium carbonate solution and treated for 48 h. The obtained lithium exchanged bentonite was filtered, washed, low-temperature dried, ground and sieved in sequence to obtain a lithium-based bentonite with a particle size of 50 μm; wherein the drying temperature was 80° C. and the drying time was 24 h. The test results are shown in Table 1. The lithium content of the ICP test was 2.96%, the increase rate of the (001) crystal plane spacing in the XRD test was 49%, and the ionic conductivity was 7.12*10 -3 S cm -1 .
[0083] According to XRD test, the (001) interplanar spacing of the bentonite raw material used in this embodiment is 1.51nm. The (001) interplanar spacing of the lithium-based bentonite obtained in this embodiment is 2.25nm. Therefore, in this embodiment, the (001) interplanar spacing of the lithium-based bentonite is 49% larger than the (001) interplanar spacing of the bentonite.
[0084] Embodiment 2-10
[0085] According to the method of Example 1, the corresponding parameters in Table 1 and Table 1 (Continued) were used. The results are shown in Table 1 and Table 1 (Continued).
[0086] Comparative Example 1
[0087] The method of Example 1 was followed, except that neither the acid treatment nor the lithium exchange treatment was performed, and the corresponding parameters in Table 1 (Continued) were followed. The results are shown in Table 1 (Continued).
[0088] Comparative Example 2
[0089] The method of Example 1 was followed, except that the acid treatment was not performed and the corresponding parameters in Table 1 (Continued) were followed. The results are shown in Table 1 (Continued).
[0090] Comparative Example 3
[0091] The method of Example 1 was followed, except that no lithium exchange treatment was performed and the corresponding parameters in Table 1 (Continued) were followed. The results are shown in Table 1 (Continued).
[0092] Table 1
[0093]
[0094]
[0095] Table 1 (continued)
[0096]
[0097]
[0098]
[0099] It can be seen from the results in Table 1 that Examples 1-10 firstly adopt the electric acid treatment and then the lithium exchange treatment, so that the performance of the lithium-based bentonite obtained is significantly better than that of Comparative Examples 1-3, wherein the increase rate of the (001) crystal plane spacing of the lithium-based bentonite is not less than 10%, the lithium content of the ICP test is not less than 0.6%, and the aluminum content of the ICP test is less than 9%, and the room temperature ionic conductivity is not less than 1×10 -4 S cm -1 .
[0100] The lithium-based bentonite of the present invention can be used for the negative electrode, positive electrode or separator of a lithium-ion battery. Compared with lithium-ion batteries made of ordinary bentonite, the rate performance and safety performance of lithium-ion batteries made of the lithium-based bentonite of the present invention are greatly improved.
[0101] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A lithium bentonite, characterized in that: The (001) crystal plane spacing of the lithium-based bentonite is 10-50% larger than the (001) crystal plane spacing of bentonite.
2. The lithium bentonite according to claim 1, wherein The (001) crystal plane spacing of the lithium-based bentonite is 30-50% larger than the (001) crystal plane spacing of bentonite.
3. The lithium bentonite according to claim 1 or 2, wherein: The mass content of lithium in the lithium-based bentonite is 0.6-3wt%, preferably 2-3wt%.
4. The lithium bentonite according to any one of claims 1 to 3, wherein: The mass content of aluminum in the lithium-based bentonite is 6-10wt%, preferably 6.8-9.3wt%.
5. The lithium bentonite according to any one of claims 1 to 4, wherein: The room temperature ionic conductivity of the lithium-based bentonite is 1×10 -4 -8×10 -3 S cm -1 , preferably 1×10 -3 -7×10 -3 S cm -1 ; And / or, the average particle size of the lithium-based bentonite is 1-100 μm.
6. A method for preparing lithium bentonite, characterized in that: The preparation method comprises: In the presence of an acidifier, the bentonite is subjected to an acid treatment to obtain an acidified bentonite; wherein the voltage of the acid treatment is 5-15V; The acidified bentonite is subjected to lithium exchange treatment with a lithiating agent to obtain lithium-based bentonite.
7. The preparation method according to claim 6, wherein: The acidulant is 1-10 mol / L sulfuric acid solution, hydrochloric acid solution or nitric acid solution; and / or, the ratio of the hydrogen ion concentration of the acidulant to the metal ion concentration of the bentonite is 8-15:1; And / or, the average particle size of the bentonite is 10-1000 μm.
8. The preparation method according to claim 6 or 7, wherein: The voltage of the acid treatment is 10-15V; And / or, the temperature of the electric acid treatment is 10-40°C, preferably 25-40°C, and the time is 1-72h, preferably 12-36h.
9. The preparation method according to any one of claims 6 to 8, wherein: The lithiumating agent is a 1-10 mol / L lithium hydroxide solution, lithium acetate solution or lithium carbonate solution; And / or, the ratio of the lithium ion concentration of the lithiating agent to the hydrogen ion concentration of the acidified bentonite is 8-15:1; preferably 10:1; And / or, the conditions of the lithium exchange treatment include: temperature of 10-40° C., preferably 25-40° C., time of 1-72 h, preferably 12-36 h.
10. The preparation method according to any one of claims 6 to 9, wherein: A post-treatment step is further included after the lithium exchange treatment, and the post-treatment at least includes washing and drying.
11. Lithium bentonite obtained according to the preparation method according to any one of claims 6 to 10.
12. Use of the lithium-based bentonite according to any one of claims 1 to 5 and 11 in lithium-ion batteries.
13. A lithium bentonite dispersion, characterized in that: The lithium-based bentonite dispersion comprises lithium-based bentonite and a dispersant; wherein the lithium-based bentonite is the lithium-based bentonite described in any one of claims 1-5 and 11.
14. The lithium bentonite dispersion according to claim 13, wherein: The content of lithium bentonite in the lithium bentonite dispersion is 1-80wt%, preferably 20-50wt%; and / or, the dispersant is selected from one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid, sodium polyacrylate, dodecylbenzene sulfonic acid and sodium dodecylbenzene sulfonate; And / or, in the lithium-based bentonite dispersion, the average particle size of the lithium-based bentonite is 0.03-1 μm.
15. Use of the lithium-based bentonite dispersion according to claim 13 or 14 in lithium-ion batteries.
Citation Information
Patent Citations
Separator for lithium-sulfur battery, and lithium-sulfur battery comprising same
CN113711434A